Dialektika Komunikasi Penegak Hukum Muslim dalam Proses Persidangan di Jakarta Selatan - Pambayun, Ellys Lestari Pambayun; Syafaat, Ahmad Syafaat M.; Al Ghifari, Hanif; Nafsih, RT Kameliana; Yuliana, Yuliana (STAINI Press, 2024)
In law enforcement, beetwen advocates, prosecutors, judges and police often do not find justice because of inappropriate communication or relational dialectical patterns. In fact, law and communication have a very significant relationship in upholding justice for society. This study approach uses communication dialectics and an Islamic perspective, while the research method takes case studies through in-depth interviews with Muslim advocates, prosecutors, judges and police around South Jakarta with field observations, both in trials at the South Jakarta District Court office and the sources' offices. The results of the research show that dialectically communication through elements of totality, movement, contradiction and praxis of law enforcers: advocates, judges, prosecutors and Muslim police are trying to apply an Islamic approach in upholding justice for society. Because by prioritizing religion, in enforcing the law through good communication, they directly and indirectly feel that good and conducive relations are often created in the courtroom, even though contradictions and controversies often occur. By communicating totally and only hoping for Allah's approval, it will create a positive effect or good influence on the trial. So, the dialectic of good communication in legal practice will give rise to fair law enforcement.